Une nouvelle fête macédonienne dans une inscription de Kibyra - Hatzopoulos, Miltiade B. (Tekmeria, 2021)
An early second century BC fragmentary inscription from Kibyra in honour of a local athlete mentions among others two victories won at festivals whichwere presided by “king Philip”, who can be no other than Philip V. The first festival was the Erotideia at a city the name of which has been lost. The second one was the Herakleia at a city in Macedonia, the name of which is not preserved. The author of the present article argues that the rst city was Thespiai in Boiotia, and that the second one was Beroia. He bases his argument on an epigram by Chrysogonos from the Anthologia Palatina explained in 1934 by Charles Edson, who on literary and numismatic evidence submitted that the Antigonids hailed from Beroia. Several inscriptions discovered locally since then leave no doubt that Herakles Kynagidas was the principal divinity of that city. Going a step further, the author connects the festival Herakleia with a list of victors from various parts of the Greek world, found at Beroia, which was known from the time of Alfred Delacoulonche, but had remained uninterpreted. A diagramma of Philip V from Amphipolis offers fresh evidence on the rules under which foreign athletes participated in Macedonian festivals.